Cognitive Load in Multimedia Learning: An Example from Teaching about Lenses - Dževdeta Dervić; Nermin Đapo; Vanes Mešić; Ratko Đokić (Seyit Ahmet Kıray, 2019)
Animations are widely used in today's science classrooms. Therefore it is very important to explore under which conditions animations are most effective. In earlier studies it has been generally shown that the effectiveness of instruction largely depends on management of cognitive load. The aim of the present study was to compare the effect of Physlet animations, printed sequences of selected animation frames and traditionally presented static pictures on understanding about lenses and levels of cognitive load. According to the results of a quasi-experiment that included forty nine high-school students, Physlet-based teaching generally leads to higher germane load and consequently to more effective learning than the traditional approach. Particularly high levels of germane load have been found for Physlet-based problems. These findings can be accounted for by the interactivity feature of Physlets.